2018
DOI: 10.1111/sjop.12488
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization through a trauma lens: Identifying who is at risk for negative outcomes

Abstract: Peer victimization is a chronic stressor that occurs within the context of peer interactions and has been robustly associated with numerous negative psychological and social adjustment problems. Although increased frequency of peer victimization has been linked to psychosocial problems, few researchers have studied the role of duration and pervasiveness of victimization (i.e., number of places it occurs). The objective of this study was to examine how frequency, duration, and pervasiveness of peer victimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…moderate adolescence-emerging group) and childhood-limited peer victimization. These findings corroborate those pointing out that persistent and high-intensity peer victimization experiences have the most pervasive impact on mental health (Arseneault, 2018;Geoffroy et al, 2018;Hanish & Guerra, 2002;Hong, Wang, Pepler, & Craig, 2020;Moore et al, 2017). Moreover, the relative weak association of childhood-limited peer victimization with mental health comorbidities could be interpreted as a dissipation over time of the effect of transient peer victimization on mental health, which has already been documented separately for externalizing and internalizing symptoms in recent quasi-experimental studies (Schoeler et al, 2019;Singham et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…moderate adolescence-emerging group) and childhood-limited peer victimization. These findings corroborate those pointing out that persistent and high-intensity peer victimization experiences have the most pervasive impact on mental health (Arseneault, 2018;Geoffroy et al, 2018;Hanish & Guerra, 2002;Hong, Wang, Pepler, & Craig, 2020;Moore et al, 2017). Moreover, the relative weak association of childhood-limited peer victimization with mental health comorbidities could be interpreted as a dissipation over time of the effect of transient peer victimization on mental health, which has already been documented separately for externalizing and internalizing symptoms in recent quasi-experimental studies (Schoeler et al, 2019;Singham et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Another key analysis presented in this paper was the mean comparison of the three CIE-A factors according to students’ gender, having shown significant mean differences in all the three factors measured by the questionnaire. In this regard, there are two issues worth of discussing: first of all, that these differences were coherent with the current literature on the gender-based differences in terms of these three factors [ 36 , 73 ], overall showing how male school students tend to be more likely to both suffer and to exert bullying-related behaviors, while females are those commonly reporting greater signs of distress and psychosocial affectation as a consequence of bullying situations, also having a greater stress perception relative to being bullied [ 6 , 24 , 34 , 84 ].…”
Section: Discussionsupporting
confidence: 71%
“…al. [ 24 ] suggested that with increasing age, youth get systematically exposed to victimization for longer periods of time; therefore, older teenagers ( i . e ., ages 16–18) get involved in longer and more pervasive victimization experiences than youth in early- and mid-adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, little is known about whether abnormalities in threat processing underlie pathways from peer victimization to anxiety among adolescents. Peer victimization represents a unique and emotionally impactful form of adversity during the adolescent years (Hong et al, 2020), and adolescents-compared to children or adults-exhibit distinct patterns of social-cognitive and affective processing that can contribute to anxiety risk. Specifically, maturation of the medial prefrontal cortex (MPFC) during adolescence contributes to increased motivation to understand others, greater self-consciousness, and heightened vigilance to (real or perceived) peer evaluation (Somerville, 2013).…”
mentioning
confidence: 99%